Validation of the ANCA-associated vasculitis patient-reported outcomes (AAV-PRO) questionnaire - Robson, J; Dawson, J; Doll, H; Cronholm, P; Milman, N; Kellom, K; Ashdown, S; Easley, E; Gebhart, D; Lanier, G; Mills, J; Peck, J; et al. (BMJ Publishing Group, 2018)
Objectives o finalise and validate a disease-specific patient-reported outcome (PRO) measure: the ANCA-associated vasculitis patient-reported outcome (AAV-PRO) questionnaire. Using a 35-item candidate questionnaire developed following 50 qualitative interviews in the UK, USA and Canada, a longitudinal survey was conducted to determine the final scale structure and validate the AAV-PRO. Methods Participants were recruited via Vasculitis UK and the Vasculitis Patient-Powered Research Network. The 35-item candidate questionnaire was completed at baseline and 3 months; UK participants completed the EuroQol-5D-5L (EQ-5D-5L), while US participants completed a test–retest exercise, 3–5 days after baseline. Scale structure was defined using exploratory factor analysis (EFA) and Rasch analysis. Convergent and known groups validity, test–retest reliability and longitudinal construct validity were assessed. Results here were 626 participants with AAV; >25% reporting ’active disease’. EFA and Rasch analysis supported a 29-item profile measure comprising six domains: ’organ-specific symptoms’, ’systemic symptoms’, ’treatment side effects’, ’social and emotional impact’, ’concerns about the future’ and ’physical function’. Mean domain scores were higher for participants with ’active disease’ versus ’remission’ (p<0.001). Construct validity was demonstrated by correlations between domain scores and the EQ-5D-5L (range r=−0.55 to 0.78), all p<0.0001. In participants reporting ’no change’ (n=97) during the test–retest, intraclass correlation coefficient values were high (range 0.89–0.96) for each domain. Conclusions he AAV-PRO, a new disease-specific PRO measure for AAV, has good face and construct validity, is reliable, feasible and discriminates among disease states.